Bioprospecting of serratiopeptidase-producing bacteria from different sources - Nair, Sreelakshmi R.; Subathra Devi, C. (Frontiers in Microbiology, 2024)
Anti-inflammatory enzymes have wide application in pharmaceutical industries. Researchers are keen to find new and efficient strains for the commercial production of enzymes. Serratiopeptidase also known as serrapeptase is an alkaline protease with potent antiinflammatory property. This multifaceted enzyme is produced by a bacterial genus named Serratia. Various species like S. marcescens, S. plymuthica, S. indica and S. picastorum are known to produce this metalloprotease enzyme. The aim of this study is to isolate, screen and identify potent serratiopeptidase producing bacteria from various sources. Twenty soil samples, silkworm gut and sugarcane stem were collected and processed in this study. Among the 60 strains,12 strains were protease positive on skim milk agar plates and showed significant protease activity. All the 12 strains were screened for serratiopeptidase by HPLC. Four strains from total isolates showed a peak at retention time of 4.66± 0.10 min which were similar to the standard. The selected potent strain VS56 showed a proteolytic activity of 21.30 units/mL and produced a total protein of 102mg/mL. The HRBC suspension results also showed a percentage of 94.6±1.00 protection which was compared with the standard diclofenac. The clot lysis potential of VS56 was 53% in 4h. Furthermore, molecular weight of protein was identified to confirm the presence of serratiopeptidase. The study hence contributed successfully to isolate, screen, and identify a potent producer for serratiopeptidase from an environmental source. This inherent advantage of the strain will undoubtedly help to contribute much to the commercial production of serratiopeptidase in near future.